2016
DOI: 10.1111/jpn.12529
|View full text |Cite
|
Sign up to set email alerts
|

In situ starch and crude protein degradation in the rumen and in vitro gas production kinetics of wheat genotypes

Abstract: The objective of this study was to determine the variation of in situ ruminal degradation characteristics of dry matter (DM), crude protein (CP) and starch (ST), and to determine the effective degradation (ED) of wheat genotypes. Further, multivariate associations of these in situ values with their corresponding in vitro gas production (GP) kinetics and laboratory measurements were evaluated using correlation and multiple linear regression analyses. Grains of 20 genotypes of wheat were characterized by proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
5
18
0
Order By: Relevance
“…These parallels between starch and CP degradation underline the strong correlation between ruminal CP and starch degradation in cereal grains, which is consistent with the results of previous studies and indicates that the protein matrix limits ruminal starch degradation as it is known from maize grains (Garnsworthy & Wiseman, 2000;McAllister et al, 1993). Similar interferences of enzymatic starch degradation by the surrounding protein matrix are supposed for soft grains, such as wheat (Seifried, Steingass, Hoffmann, et al, 2017) or barley (Svihus, Uhlen, & Harstad, 2005). Hence, degradation of the protein matrix seems to limit starch degradation.…”
Section: In Situ Degradation Characteristicssupporting
confidence: 90%
See 2 more Smart Citations
“…These parallels between starch and CP degradation underline the strong correlation between ruminal CP and starch degradation in cereal grains, which is consistent with the results of previous studies and indicates that the protein matrix limits ruminal starch degradation as it is known from maize grains (Garnsworthy & Wiseman, 2000;McAllister et al, 1993). Similar interferences of enzymatic starch degradation by the surrounding protein matrix are supposed for soft grains, such as wheat (Seifried, Steingass, Hoffmann, et al, 2017) or barley (Svihus, Uhlen, & Harstad, 2005). Hence, degradation of the protein matrix seems to limit starch degradation.…”
Section: In Situ Degradation Characteristicssupporting
confidence: 90%
“…Various studies using maize grains showed that the protein composition of the grains influenced ruminal degradation (McAllister, Bae, Jones, & Cheng, ; McAllister & Cheng, ; McAllister, Phillippe, Rode, & Cheng, ; McAllister, Rode, Major, Cheng, & Buchanan‐Smith, ; Seifried, Steingass, Schipprack, et al., ). Triticale grains exhibited degradation parameters and ED lying between those of rye from the present study and wheat analysed using the same methodical approach (Seifried, Steingass, Hoffmann, et al., ). Different studies demonstrated that the triticale protein properties (e.g., solubility) fall between the properties of wheat and rye proteins (Chen & Bushuk, ,b).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The negative relationship between starch and CP, which has also been shown for several cereal grains by Krieg et al (2018) For spelt kernels, the rate of GP was on average 11.4%. This is equal or close to the mean rate of GP determined with the same method for varieties of wheat (11.4%), triticale (11.5%) and barley (11.1%), and lower than that of rye (12.5%) but higher than that of maize (7.1%) (Krieg et al, 2017;Seifried, Steingass, Hoffmann, & Rodehutscord, 2016;Seifried, Steingass, Schipprack, et al, 2016). Thus, ruminal starch degradation characteristics and effects on pH in the rumen may be very similar to those known for wheat and barley, meaning that high amounts of spelt kernels in a ration of dairy cows have the risk of causing an undesirable drop of ruminal pH value.…”
Section: Spelt Kernelssupporting
confidence: 77%
“…The c value of ST, and the mean CP concentration of grains, decreased from location L1 to location L3, which was also reflected in a positive correlation between CP concentration and the c value of ST. Contrary to this, CP concentration was reported to be negatively correlated with ruminal ST degradation in maize and soft wheat grains (Seifried, Steingass, Hoffmann, & Rodehutscord, 2017; Seifried et al., 2016). Seifried et al.…”
Section: Discussionmentioning
confidence: 95%